The Freeman, and Other Poems - Glasgow, Ellen Anderson Gholson, 1873-1945 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Freeman, and Other Poems" by Ellen Anderson Gholson Glasgow is a collection of poetry written in the early 20th century. This book explores themes of freedom, human experience, and existential reflections, showcasing Glasgow's skill in capturing the complexities of life through vivid imagery and emotional depth. The poems in this collection cover a wide range of topics, reflecting on concepts such as despair, love, justice, and the search for truth. In "The Freeman," Glasgow presents a powerful exploration of the liberating yet burdensome experience of despair, while in "A Prayer" and "A Battle Cry," she expresses the yearning for courage and the human spirit's resilience in the face of adversity. Other poems, like "Death-in-Life" and "Resurrection," delve into mortality and the human experience beyond death, using haunting imagery to evoke profound emotional responses. Throughout the collection, Glasgow's use of lyrical language and poignant metaphors creates a rich tapestry that resonates with readers, prompting deep contemplation of life's trials and triumphs. (This is an automatically generated summary.)
Release date is 2021-06-09
Tim Lindell, Chuck Greif and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: American poetry